Short- and midterm outcomes of coronary artery bypass surgery performed by surgeons in training - Yap, C.; Andrianopoulos, N.; Dinh, D.; Billah, B.; Rosalion, A.; Smith, J.; Shardey, G.; Skillington, P.; Tatoulis, J.; Mohajeri, M.; Yii, M.; Reid, Christopher (The American Association of Thoracic Surgery, 2009)
Objective: The effect of training on outcomes in cardiac surgery is poorly studied. We aimed to study the results of coronary artery bypass grafting procedures performed by surgeons in training across our state with respect to short- and midterm postoperative outcomes. Methods: All coronary artery bypass grafting surgeries performed by trainee surgeons between July 2001 and December 2006 were compared with those performed by consultant surgeons using mandatory prospectively collected statewide data. Early mortality; prolonged ventilation or intensive care unit stay; return to operating theater for bleeding, stroke, myocardial infarction, or renal failure; and 5-year survival were compared using propensity score analysis. Results: A total of 7745 surgeries were included in this study. Trainees performed 983 (13%) surgeries. Trainee surgeries had longer perfusion and crossclamp times. Crude early postoperative outcomes were similar between trainee and consultant surgeries. After propensity score adjustment, early outcomes remained similar, with the exception of myocardial infarction (0.8% in trainee surgeries vs 0.4% in consultant surgeries, P = .046). Adjusted 1-, 3-, and 5-year survivals were similar between trainee and consultant surgeries: 95.3% versus 95.5%, 90.8% versus 92.0%, and 86.3% versus 87.1%, respectively. Conclusion: Coronary artery bypass grafting performed by trainee surgeons within a supervised program is safe with acceptable short- and midterm outcomes. © 2009 The American Association for Thoracic Surgery.